Application of Ultrasonic Sensor and IR Sensor in Automatic Alcohol Hand Sanitizer - Wirote Jongchanachavawat; Bureerak Sungkongmueng; Chaleedol Inyasri; Ittipat Roopkom; Noppon Mingmuang; Pichamol Putthed; Atiwat Srithammakan; Boonpi Chinowan; Patcharapon Pathomphomma; Peemongkol Kumngern; Suphat Bunyarittikit; Patchamon Jongchanachavawat (My University, 2023)
Hygiene is necessary to maintain human health.Hygiene keeps the body clean and free from germs, preventing the spread of diseases, which has been especially important during the COVID-19 pandemic.For this reason, we designed automatic alcohol hand sanitizers (AAHSs): one with an IR sensor and one with an ultrasonic sensor.The sanitizers will help prevent germs from spreading via the hands of people because no part of each device need be touched during its use.The AAHS with the ultrasonic sensor has various advantages over that with the IR sensor: it is 32% cheaper to produce, easier to configure and maintain, has a higher average score for user satisfaction, is smaller and more portable, and can use rechargeable batteries.In addition, its low cost makes it more suitable for commercialization.It can also be installed both outdoors and indoors.In an outdoor test, it was demonstrated to operate flawlessly.This paper includes useful information on the components of the AAHSs with the two types of sensor and an evaluation of their performance using confusion matrices.
Keywords: Hand sanitizer; Fire Detection and Safety Systems